PREDIKSI FINANCIAL DISTRESS PADA SEKTOR PERTAMBANGAN - Handayani, Anita (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
Financial distress shows the condition of the company unable to fulfill its smooth obligations. Financial difficulties if not handled properly will bring the company into bankruptcy. Bankruptcy predictions can use the Altman, Springate, Grover, Zmijewski methods. The results showed that the accuracy of the Springate model predicts financial distress by 73% compared to other models. And sequentially followed by Altman’s model of 54%, and the grover model of 35% and the last is the zmijewski model of 22%.